Microcultural Study of Bacterial Size Changes and Microcolony and Ultramicrocolony Formation by Heterotrophic Bacteria in Seawater - Torrella, Francisco (1981)
With a microculture technique and time-lapse, phase-contrast photomicrography, it was possible to follow the division of individual cells and the development of microcolonies of bacteria in freshly collected marine water samples. A certain number of marine bacteria, upon inoculation onto a nutrient rich agar surface, displayed an increase in size as well as a high growth rate. Other bacteria were identified as very small marine bacteria (ultramicrobacteria). These had a very slow growth rate when inoculated onto a nutrient-rich agar surface. These latter cells formed very small microcolonies (ultramicrocolonies), and cell size did not increase significantly. These two types of marine heterotrophs could be described in terms of zymogenous and autochthonous bacteria, a concept used by Winogradsky for describing soil microorganisms.